Determination of Cytotoxic Thermal Dose During HIFU Ablation - Nandlall, S; Bazan-Peregrino, M; Mo, S; Coussios, C (2012)
Thermal dose has been proposed for various hyperthermic cancer treatment modalities as a measure of heat-induced cell and tissue damage. However, many of the models that are currently used for calculating thermal dose have not been validated or suitably adapted for the elevated temperatures and rates of heating encountered during ablation by High-Intensity Focused Ultrasound (HIFU). This work quantifies the performance of the widely employed Cumulative Equivalent Minutes at 43°C (CEM43) thermal dose metric under HIFU-relevant heating. A total of 36 agar phantoms were embedded with different human cancer cell lines (PC3, 22RV1, or ZR75.1) as well as calcein AM and propidium iodide assays. The phantoms were cast in sterile molds with internal dimensions of 7 cm × 7 cm × 2 mm. Using a water bath, 12 of the phantoms were treated with mild hyperthermia (43-46°C for up to 60 minutes), while another 12 were subjected to HIFU-relevant temperature profiles (60-80°C peak temperature, 2-3°C/s peak heating rate). In each of the remaining 12 phantoms, 8 HIFU exposures were carried out in a 37°C water tank (1.067 MHz, 95% duty cycle, 3-6 MPa peak rarefaction pressure, 2-20 s exposure duration). Cavitation emissions were monitored passively with a detector transducer that was confocally and co-axially aligned with the HIFU source. Cell death was quantified by measuring the locally averaged fluorescence intensity of the assays relative to unheated and severely heat-shocked phantoms. The results show that the CEM43 dose required to achieve the same level of heat-induced cell death varies considerably across cell lines, and that inertial cavitation can cause significant mechanical damage at ablation-relevant intensities even when no significant thermal dose is delivered (CEM43 < 5 s). These findings demonstrate the need for improved models of cell death at ablation-relevant temperatures. © 2012 American Institute of Physics.